The Influence of Social Media Instagram on Generation Z's Political Participation - Haris, Abdul; Aksa, Yudha Asmara Dwi; Prastyo, Alif Bagas (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
In 2023, political contents are easily accessible on social media accounts. In this regard, a social media account called @pinterpolitik has the potential to influence generation z in political participation. Political participation has various elements such as electoral participation, consumer participation, party activity, protest activity and contact activity. The present study analyzed the influence of @pinterpolitik on generation z's political participation. This research uses quantitative methods with a descriptive approach. The results of this study found that social media accounts have a positive effect on political participation. The results show that the Instagram account @pinterpolitik influences he political participation of generation z. This high respondent achievement is on the indicator of electoral participation. Even though it has a high respondent achievement, this research has only reached the electoral stage, not to the stage of voting and coming to the polling station location. However, this research has the disadvantage of not being too specific about generation z's political participation and the @pinterpolitik account that influences generation z's political participation.